Influence of morphological characteristics on the deposition of low-density lipoprotein in intracranial bifurcation aneurysms - Tian, Yuqing; Li, Xiao; Zhao, Bing; Zhang, Jianjian; Liang, Fuyou (Physics of fluids (1994), 2023)
The increasingly demonstrated association of wall enhancement (WE) measured by vascular wall imaging with the instability/rupture of intracranial aneurysms (IAs) implies the significance of investigating the transport and accumulation of blood substances [e.g., low-density lipoprotein (LDL), lipoprotein (a)] related to WE in IAs. In the present study, we perform numerical simulations to explore the relationships between the distribution/severity of LDL deposition on the lumen surface and the morphological characteristics of aneurysm and its adjacent arteries as well as the underlying fluid dynamic mechanisms. Bifurcation aneurysms located at the middle cerebral artery are selected as the subject of investigation and for which both idealized and patient-specific models are built. Studies on the idealized models reveal that the aneurysm–parent (AP) artery angle is more powerful than other morphological parameters [e.g., daughter–parent (DP) artery angle, nonsphericity index (NI) of aneurysm] in determining the severity of LDL deposition. A bleb (i.e., secondary sac) can enhance local LDL deposition, especially when located in an LDL deposition-prone aneurysm wall region. In patient-specific models, the dominant effect on the LDL deposition of the AP angle remains identifiable, whereas the effects of the DP angle and NI are overwhelmed by confounding factors. Enhanced LDL deposition prefers to appear in wall regions perpendicular to the intra-aneurysmal vortex centerline. In comparison with wall shear stress magnitude, the normal-to-tangential near-wall velocity ratio and particle residence time can better predict the localization of enhanced LDL deposition.